Variant connective tissue (joint hypermobility) and dysautonomia are associated with multimorbidity at the intersection between physical and psychological health. Issue 4 (22nd November 2021) - Csecs, Jenny L. L.; Dowell, Nicholas G.; Savage, Georgia K.; Iodice, Valeria; Mathias, Christopher J.; Critchley, Hugo D.; Eccles, Jessica A.
Abstract: The symptoms of joint hypermobility extend beyond articular pain. Hypermobile people commonly experience autonomic symptoms (dysautonomia), and anxiety or related psychological issues. We tested whether dysautonomia might mediate the association between hypermobility and anxiety in adults diagnosed with mental health disorders and/or neurodevelopmental conditions (hereon referred to as patients), by quantifying joint hypermobility and symptoms of autonomic dysfunction. Prevalence of generalized joint laxity (hypermobility) in 377 individuals with diagnoses of mental health disorders and/or neurodevelopmental conditions was compared to prevalence recorded in the general population. Autonomic symptom burden was compared between hypermobile and non‐hypermobile patients. Mediation analysis explored relationships between hypermobility, autonomic dysfunction, and anxiety. Patient participants had elevated prevalence of generalized joint laxity (38%) compared to the general population rate of 19% (odds ratio: 2.54 [95% confidence interval: 2.05, 3.16]). Hypermobile participants reported significantly more autonomic symptoms. Symptoms of orthostatic intolerance mediated the relationship between hypermobility and diagnosis of an anxiety disorder. Patients with mental health disorders and/or neurodevelopmental conditions have high rates of joint hypermobility. Accompanying autonomic dysfunction mediates the association between joint hypermobility and clinical anxiety status. Increased recognition of this association can enhance mechanistic understanding and improve the management of multimorbidity expressed in physical symptoms and mental health difficulties.